Autocrine glutamatergic transmission for the regulation of embryonal carcinoma stem cells - Teng, Lin (Oncotarget, 2016)
Glutamate behaves as the principal excitatory neurotransmitter in the vertebrate central nervous system and recently demonstrates intercellular signaling activities in periphery cancer cells. How the glutamatergic transmission is organized and operated in cancer stem cells remains undefined. We have identified a glutamatergic transmission circuit in embryonal carcinoma stem cells. The circuit is organized and operated in an autocrine mechanism and suppresses the cell proliferation and motility. Biological analyses determined a repertoire of glutamatergic transmission components, glutaminase, vesicular glutamate transporter, glutamate NMDA receptor, and cell membrane excitatory amino-acid transporter, for glutamate biosynthesis, package for secretion, reaction, and reuptake in mouse and human embryonal carcinoma stem cells. The glutamatergic components were also identified in mouse transplanted teratocarcinoma and in human primary teratocarcinoma tissues. Released glutamate acting as the signal was directly quantified by liquid chromatography coupled with tandem mass spectrometry (LC-MS/MS). Genetic and pharmacological abolishment of the endogenously released glutamate-induced tonic activation of the NMDA receptors increased the cell proliferation and motility. The finding suggests that embryonal carcinoma stem cells can be actively regulated by establishing a glutamatergic autocrine/paracrine niche via releasing and responding to the transmitter.